2023
DOI: 10.3390/antiox12030559
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Main Protease Targets Host Selenoproteins and Glutathione Biosynthesis for Knockdown via Proteolysis, Potentially Disrupting the Thioredoxin and Glutaredoxin Redox Cycles

Abstract: Associations between dietary selenium status and the clinical outcome of many viral infections, including SARS-CoV-2, are well established. Multiple independent studies have documented a significant inverse correlation between selenium status and the incidence and mortality of COVID-19. At the molecular level, SARS-CoV-2 infection has been shown to decrease the expression of certain selenoproteins, both in vitro and in COVID-19 patients. Using computational methods, our group previously identified a set of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
0
9
0
1
Order By: Relevance
“…The impairment of antioxidant defense is due to SARS-CoV-2 infection. Selenium and selenoproteins play a major role in combating oxidative stress in response to SARS-CoV-2 infections [ 324 , 325 ]. Several experiments from different countries have demonstrated that low serum levels are present in COVID-19 patients [ 326 , 327 ].…”
Section: Selenoproteins and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The impairment of antioxidant defense is due to SARS-CoV-2 infection. Selenium and selenoproteins play a major role in combating oxidative stress in response to SARS-CoV-2 infections [ 324 , 325 ]. Several experiments from different countries have demonstrated that low serum levels are present in COVID-19 patients [ 326 , 327 ].…”
Section: Selenoproteins and Human Healthmentioning
confidence: 99%
“…Interestingly, GP X 1 significantly binds with the inactive Mpro mutant (C145A), but no interaction is observed between GPx1 and wild-type Mpro [ 342 , 343 ]. Based on this, Gallardo et al investigated experimentally the cleavage of the GPx1 10-mer peptide by Mpro, but no cleavage was observed [ 324 ]. It can be concluded that selenocysteine is significantly different from glutamine at the cleavage site.…”
Section: Selenoproteins and Human Healthmentioning
confidence: 99%
“…Die Arbeitsgruppe von Ethan Will Taylor an der University of North Carolina in Greensboro, USA, hat vor kurzem einen mechanistischen Zusammenhang zwi-schen dem Covid-Virus Sars-CoV-2 und dem Selenstoffwechsel nachgewiesen. 3) Vorher gab es Hinweise darauf, dass Viren die Produktion von Selenoproteinen behindern, indem sie in die Genregulation eingreifen. Nach den neuen Ergebnissen gehen sie gegen die Proteine selbst vor: Den Forscher:innen zufolge spaltet die Protease des Virus drei menschliche Selenoproteine und macht sie damit funktionsuntüchtig.…”
Section: Covid-19 Und Krebsunclassified
“…Other strong candidates for proteolysis by Mpro included sites in TXNRD1 and SELENOP. Synthetic peptides corresponding to all three of these putative cleavage sites in human selenoproteins have been found to be cleaved in vitro by recombinant Mpro using synthetic peptides and MS to identify the cleavage products (80) .…”
Section: Selenoprotein Mechanismsmentioning
confidence: 99%